2017
DOI: 10.1136/jnnp-2017-316603
|View full text |Cite
|
Sign up to set email alerts
|

CSF β-amyloid and white matter damage: a new perspective on Alzheimer’s disease

Abstract: Objective: To assess the connection between amyloid pathology and white matter (WM) macro-and micro-structural damage in demented patients compared with controls.Methods: Eighty-five participants were recruited: 65 with newly diagnosed Alzheimer's disease (AD), non-AD dementia or mild cognitive impairment (MCI), and 20 age-and sex-matched heatlhy controls. β-amyloid 1-42 (Aβ) levels were determined in cerebrospinal fluid (CSF) samples from all patients and 5 controls. Among patients, 42had pathological CSF Aβ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…AD‐related damage may cause white matter damage through Wallerian degeneration occurring secondary to neuronal insult (McAleese et al, ). A recent study by Pietroboni et al () found abnormal β‐amyloid to be the best predictor of WM lesion load within a cohort with AD. Low CSF β‐amyloid levels indicate impaired clearance from, and accumulation within, the brain and may detect abnormalities earlier than positron emission tomography (PET) (Palmqvist, Mattsson, & Hansson, ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…AD‐related damage may cause white matter damage through Wallerian degeneration occurring secondary to neuronal insult (McAleese et al, ). A recent study by Pietroboni et al () found abnormal β‐amyloid to be the best predictor of WM lesion load within a cohort with AD. Low CSF β‐amyloid levels indicate impaired clearance from, and accumulation within, the brain and may detect abnormalities earlier than positron emission tomography (PET) (Palmqvist, Mattsson, & Hansson, ).…”
Section: Discussionmentioning
confidence: 97%
“…ADrelated damage may cause white matter damage through Wallerian degeneration occurring secondary to neuronal insult (McAleese et al, 2017). A recent study by Pietroboni et al (2018) found abnormal β-amyloid to be the best predictor of WM lesion load within a cohort Despite showing statistically significant associations with β-amyloid, we observed no associations with tau for either WM-hyper or WM-hypo ( Figure 6), but work by McAleese et al (2015) found a closer independent correlation between WM lesion load in AD with tau than β-amyloid. This difference may be related to a lower prevalence of tau in our cohort, which includes primarily cognitively intact, nondemented individuals (Harrington et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These data gain interest since we previously demonstrated in a paper about CSF biomarkers of neurodegeneration and WM damage in patients with Alzheimer's disease (AD) 26 that CSF Aβ levels were instead a predictor for WM-LL accumulation. The myelin model combines the occurrence of WM metabolic damage with Aβ deposition 27 .…”
Section: Discussionmentioning
confidence: 99%